2014
DOI: 10.1002/chem.201403956
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycles from α‐Aminonitriles

Abstract: Owing to their various modes of reactivity, α-aminonitriles represent versatile building blocks for the construction of a wide range of nitrogen heterocycles. The present Concept article focuses on synthetic methodologies using their bifunctional nature which is the basis of their reactivity as α-amino carbanions and as iminium ions. Reactions exclusively taking place on either the amine or on the nitrile moiety will not be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(23 citation statements)
references
References 145 publications
(163 reference statements)
0
22
0
1
Order By: Relevance
“…The asymmetric Strecker reaction is one of the most useful and important reactions for carbon‐carbon bond formation, providing enantioenriched α‐amino nitriles . This kind of compounds are very useful building blocks in organic synthesis, because they are precursors for value‐added products such as α‐amino acids and derivatives, 1,2‐diamines, or nitrogen heterocycles . Despite the great achievements and the impressive progress in the enantioselective Strecker reactions, the main examples are focused on acyclic imines, while the catalytic asymmetric Strecker reactions with cyclic imines are barely studied.…”
Section: Methodsmentioning
confidence: 99%
“…The asymmetric Strecker reaction is one of the most useful and important reactions for carbon‐carbon bond formation, providing enantioenriched α‐amino nitriles . This kind of compounds are very useful building blocks in organic synthesis, because they are precursors for value‐added products such as α‐amino acids and derivatives, 1,2‐diamines, or nitrogen heterocycles . Despite the great achievements and the impressive progress in the enantioselective Strecker reactions, the main examples are focused on acyclic imines, while the catalytic asymmetric Strecker reactions with cyclic imines are barely studied.…”
Section: Methodsmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16][17][18] The pioneering chemical synthesis of α-amino acids reported by Adolph Strecker in 1850 made use of their close relationship with α-aminonitriles and even today, the Strecker synthesis is still used for the industrial scale synthesis of α-amino acids like methionine. 19 Due to the strong anion stabilizing capacity of the nitrile group and the latent iminium ion reactivity, [20][21][22][23] α-aminonitriles are not only useful precursors to amino acids but also versatile building blocks for the synthesis of a wide variety of nitrogen-containing compounds 24, 25 including diverse N-heteroarenes, [26][27][28] aliphatic amine derivatives 29,30 or alkaloids [31][32][33][34][35][36][37][38][39] . We found that N-mono-and N-unsubstituted α-aminonitriles derived from aromatic or heteroaromatic aldehydes can be deprotonated quantitatively in α-position to furnish stabilized α-aminocarbanion equivalents and in contrast to their counterparts derived from aliphatic aldehydes, no N-protection is required.…”
Section: Page 1 Of 24 Acs Paragon Plus Environmentmentioning
confidence: 99%
“…The acetal 6 j could be selectively deprotected . Substrate 6 k underwent a variety of chemoselective transformation in good to excellent yield including hydrogenation, reductive decyanation,, dehydrocyanation,, and ketone reduction. Building block 6 q also underwent reductive decyanation, diastereoselectively yielding substrate 15 g bearing an ester moiety.…”
Section: Figurementioning
confidence: 99%